Correction: Rapid fabrication of functionalised poly(dimethylsiloxane) microwells for cell aggregate formation. (13th April 2017) - Forget, A.; Burzava, A. L. S.; Delalat, B.; Vasilev, K.; Harding, F. J.; Blencowe, A.; Voelcker, N. H.
Abstract : Correction for 'Rapid fabrication of functionalised poly(dimethylsiloxane) microwells for cell aggregate formation' by A. Forget et al., Biomater. Sci., 2017, 5, 828–836.